Clinical significance of colorectal polyp detection on colonoscopy insertion. Issue 1 (February 2019) - Sakamoto, Taku; Ramaraj, Raji; Tomizawa, Yutaka; Cho, Hourin; Matsuda, Takahisa; Saito, Yutaka
Background: Colorectal lesions are generally evaluated during the withdrawal phase of colonoscopy. Minimising the risk of missed lesions is crucial to determine an appropriate future surveillance colonoscopy interval. Objective: This study aimed to evaluate the clinical significance of detecting sigmoid colon lesions during the insertion phase. Methods: This retrospective study included 172 consecutive patients undergoing colonoscopy between October 2017 and April 2018. The total number of detected polyps, mean polyps per procedure, mean polyps per positive procedure, and histological and clinical characteristics of detected lesions were recorded. The primary endpoint was the difference in sigmoid colon polyp detection rates during insertion and withdrawal. Results: A total of 172 colonoscopies were performed for each patient and 322 lesions were detected. Sixty-two (19%) polyps were detected during insertion, 312 (97%) during withdrawal, and 52 (16%) during both insertion and withdrawal. Although all polyps except for those in the sigmoid colon could be detected during withdrawal, 10 of 87 (11%) polyps in the sigmoid colon could only be detected during insertion. Conclusions: In this study, attempts to detect polyps, even in the insertion phase, showed the clinical significance to decrease the risk of missed adenomatous polyps in the sigmoid colon.